Enhancing Energy Efficiency in Irrigation A Socio-Technical Approach in South India - Sagebiel, Julian; Kimmich, Christian; Müller, Malte; Hanisch, Markus; Gilani, Vivek (SpringerBriefs in Environmental Science, 2016)
This SpringerBrief reviews currently applied and potential solutions for improving the efficiency and quality of rural electricity supply in India, a major bottleneck for agricultural development. It provides background on the current state of supply and reviews recent and ongoing research and development projects. One selected project, designed and conducted by the authors, is outlined in detail. The research findings, project implementation, and evaluation are intended to provide development practitioners, policy makers, and applied researchers with experience from the field. At the core of this Brief is the integration of technical and social solutions, emphasizing the role of collective action, and the merits and demerits of small-scale, technically simple measures.